Embedded based remote monitoring and controlling system - Abdul Muiz, Roomai Nor (2010)
Remote monitoring and controlling system is a system that capable of measuring several ecological parameters in distance away room and capable setting the condition into desire environment through wireless communication system from central room. Depending on its application needs, various technologies as well as improvements have been designed, developed and implemented. In this case, a Zigbee based wireless communication approach is considered to monitor and control various parameters in remote location. This wireless technology offers an effective and noise-free communication between the central and remote room arrangement. Several sensors are equipped in each remote location to measure environmental parameters and these measurements are sent to the central office for storage and analysis purpose. In addition, the central office capable of instruct several command to remote location for output control execution. These features offer an efficient way to maintain condition in the room and allow user to obtain caution on occurrence of any abnormal conditions like parameters exceeding human comfort zone